2013
DOI: 10.1007/s11999-012-2552-8
|View full text |Cite
|
Sign up to set email alerts
|

High Survival of Modular Tapered Stems for Proximal Femoral Bone Defects at 5 to 10 Years Followup

Abstract: Background Currently, the two most commonly used options for the revision of femoral components in North America are: cylindrical, nonmodular, cobalt-chromium stems and tapered, fluted, modular, titanium (TFMT) stems. Previous reports have cited high failure rates with cylindrical cobalt chrome stems in large femoral defects but the longer term survival of the fluted stems is unknown. Questions/PurposesWe examined the 5-to 10-year survival of TFMT stems implanted for severe femoral defects. Methods We reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
87
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 33 publications
8
87
0
7
Order By: Relevance
“…Given the failures of monoblock cylindrical stems in patients with the most severe defects (Paprosky Type IIIB/IV) [26], it has been suggested that these patients may be best treated with a modular tapered stem; however, few studies have specifically studied this issue [21,27,28]. Stems with a tapered distal geometry may be able to gain stability in a shorter isthmic segment than a cylindrical stem, whereas their modularity allows the surgeon to adjust length, offset, and version.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the failures of monoblock cylindrical stems in patients with the most severe defects (Paprosky Type IIIB/IV) [26], it has been suggested that these patients may be best treated with a modular tapered stem; however, few studies have specifically studied this issue [21,27,28]. Stems with a tapered distal geometry may be able to gain stability in a shorter isthmic segment than a cylindrical stem, whereas their modularity allows the surgeon to adjust length, offset, and version.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, modularity of the stem allows for impaction of the distal segment until secure axial stability is obtained and then using the varied available modular options in the proximal segment to adjust for leg length, offset, and version. However, there are few data describing survivorship and hip scores associated with this newer stem design in patients with severe femoral bone loss [21,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple reports from one institution have demonstrated the success of modular tapered stems for cases of proximal femoral bone loss. The authors demonstrated high mid-term survival rates of 90-94%, maintenance or improvement of bone stock and low subsidence rates [4,13]. Higher outcome scores, better bone restoration and less intraoperative fractures were also found with modular tapered stems compared with fully porous coated cobalt-chromium stems [11,12].…”
Section: Discussionmentioning
confidence: 90%
“…Cortical deficiency extending to between lesser trochanter and isthmus the modular junction are reported in the literature on multiple stem designs [3][4][5][6][7]. Manufacturers have developed methods for strengthening the taper junction.…”
Section: Cmentioning
confidence: 99%
“…Here, the fixation zone in the femur usually lies higher up the stem resulting in the use of longer revision stems with a bypass of the isthmus. As a result, there is a higher risk of intraoperative fracture, which helps explain why van Houweligen and colleagues [6] observed an intraoperative fracture percentage of 16% with this type of stem.…”
mentioning
confidence: 96%